Influence of Training Programmes on Access to County Vocational Education and Training Institutions in Makueni County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of this study was to investigate the influence of training programmes on access to County Vocational Education and Training institutions in Makueni County, Kenya. The study was informed by the existence of a large number of youths in the County who have not enrolled in CVETIs hence leading to high population of idle youths with low or no relevant employable skills which contributes to increased dependency ratio, high unemployment rates, engagement in drug and substance abuse and other social-evils. The study sought to investigate whether, the career guidance services influence access to County Vocational Education and Training Institutions in Makueni County, Kenya. The study was guided by Human Capital Theory (HCT). The study employed descriptive research design. The study targeted 28 registered Public Vocational institutions in Makueni County. The study used stratified simple random sampling and purposive sampling techniques to obtain a random sample of 21 managers, 87 instructors and 316 trainees drawn from 21 randomly selected Vocational institutions. Questionnaires, interview schedule and an observation check list were used to collect data. Data were processed and analyzed qualitatively and quantitatively. Quantitative analysis used descriptive and inferential statistics computed using a computer programme (SPSS version 23 computer package). Descriptive statistics were generated and used in describing and discussing the research findings. Statistical tests were done using a T-test and one-way analysis of variance (ANOVA) at 95% Confidence Interval of the difference (α=0.05). The finding of the study revealed that, vocational training courses have not kept the phase of advancing technology in the industry and they less meet the labour market requirements, hence not attracted prospective trainees who meet the minimum admission requirements. Based on this findings the study recommended that, there is need to re-plan the Vocational Education and Training curriculum in Kenya with the KCSE graduates in mind as opposed to their historical establishment as village youths polytechnics.